Information Systems Integration - the Proposal of Classification - Polak, Przemysław (Advanced Information Technologies for Management – AITM 2009, 2009)
The term "integration" refers to many aspects belonging to the area of interest of computer science and business informatics. Business informatics research usually considers independently integration of information systems within an organization and interorganizational integration. The author argues that this classification is obsolete in terms of current research, business needs, and advances in information technology. For that reason, he proposes a new classification of the information systems integration in terms of the organizational scope of the integration: intraorganizational, extraorganizational and multiorganizational.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 85, s. 199-206